Case report of an anatomic variation of the buccal nerve (branch of Trigeminal Nerve - V3) - Ferreira, Beatriz C.; Freire, Alexandre R.; Junqueira, Jose A. G. [UNESP]; Botacin, Paulo R. [UNESP]; Prado, Felippe B.; Rossi, Ana C. (Soc Anatomica Espanola, 2021)
One of the branches of the mandibular nerve is the buccal nerve. It is responsible for sensory innervating of the buccal gingiva of the lower teeth and the buccal mucosa of the cheek. The aim of this study was to report a case of a cadaver with an anatomic variation of the buccal nerve (branch of Trigeminal Nerve - V3). During a routine Anatomy class, from the observation of a 43-year-old female cadaver head, a unilateral (left side) communicating branch between the buccal branch of the trigeminal nerve and the inferior alveolar nerve was found. The knowledge of anatomical variations is essential to avoid errors and to give the patient adequate clinical management during specific dental and surgical procedures in each case.
Keywords: Anatomic variation; Buccal nerve; Clinical Anatomy; Macroscopic human anatomy